Acute abdomen after vertebroplasty-A rare complication - Xiao-ming Zhao; Xiao-xiao Lou; An-fa Chen; Yin-gang Zhang (Frontiers in Surgery)
IntroductionIn recent years, as the concept of minimally invasive treatment has been accepted by the majority of patients, the application of percutaneous vertebroplasty in osteoporotic vertebral compression fractures has gradually increased, and research on the adverse complications of bone cement leakage has gradually deepened.CaseHere, we report a rare case of acute pancreatitis after vertebroplasty. The patient had no previous history of pancreatitis and presented with obvious abdominal pain after vertebroplasty. Abdominal CT examination revealed that the leaking bone cement penetrated the anterior wall of the L1 vertebral body into the diaphragm, and the heat released by the polymerization reaction caused inflammation and damage to the adjacent pancreas, resulting in poor blood flow to the pancreatic tissue and leading to acute pancreatitis. Early postoperative symptomatic treatment was given to the patient, and the corresponding symptoms were gradually relieved. During postoperative follow-up, the leaking cement did not degrade, but the patient had no symptoms.ConclusionLesions of adjacent organs caused by bone cement leakage are rare, and clinicians often ignore the association between such complications and vertebroplasty. This case report will provide guidance and a reference for clinicians.